Fucoxanthin: A Promising Phytochemical on Diverse Pharmacological Targets - Mumu, Mumtaza; Das, Ayan; Emran, Talha Bin; Mitra, Saikat; Islam, Fahadul; Roy, Arpita; Karim, Md. Mobarak; Das, Rajib; Park, Moon Nyeo; Chandran, Deepak; Sharma, Rohit; Khandaker, Mayeen Uddin; et al. (Frontiers in Pharmacology, 2022)
Fucoxanthin (FX) is a special carotenoid having an allenic bond in its structure. FX is extracted from a variety of algae and edible seaweeds. It has been proved to contain numerous health benefits and preventive effects against diseases like diabetes, obesity, liver cirrhosis, malignant cancer etc. Thus, FX can be used as a potent source of both pharmacological and nutritional ingredient to prevent infectious diseases. In this review, we gathered the information regarding the current findings on antimicrobial, antioxidant, anti-inflammatory, skin protective, anti-obesity, antidiabetic, hepatoprotective and other properties of FX including its bioavailability and stability characteristics.. This review aims to assist further biochemical studies in order to develop further pharmaceutical assets and nutritional products in combination with FX and its various metabolites.